ANALISIS MODEL REKRUITMEN MAHASISWA PENERIMA BEASISWA KARTU INDONESIA PINTAR (KIP)KULIAH DI UNIVERSITAS ISLAM JEMBER - Ahmad Zainullah Hasan; Syarkawi Syarkawi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Higher education serves as a fundamental pillar in developing competitive, ethical, and high-quality human resources. In accordance with Law No. 12 of 2012 on Higher Education, the Indonesian government is obligated to expand access and learning opportunities for all citizens. One of the strategic initiatives to achieve this goal is the Smart Indonesia Card for College (Kartu Indonesia Pintar – KIP Kuliah) program, which provides educational assistance to outstanding students from low-income families, enabling them to pursue higher education without financial burden. This study aims to analyze the recruitment model of KIP Kuliah scholarship recipients at the Islamic University of Jember and to evaluate its effectiveness based on the official guidelines of the Ministry of Education, Culture, Research, and Technology. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document analysis involving scholarship administrators, academic advisors, and student beneficiaries. Data were analyzed using the Miles, Huberman, and Saldaña interactive model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that the recruitment process for KIP Kuliah recipients at the Islamic University of Jember has been systematically implemented in accordance with national guidelines. The selection stages include administrative screening, academic potential tests, interviews, and additional assessments on Ahlussunnah wal Jama’ah theological understanding and Qur’an reading ability—reflecting the Islamic values embedded in the university’s character education. The program has effectively enhanced access to higher education, fostered learning motivation, and promoted upward social mobility among students from economically disadvantaged backgrounds. Nevertheless, several challenges remain, such as mismatches between socioeconomic data and the Integrated Social Welfare Data (DTKS), limited digital literacy, and administrative complexity. Therefore, capacity building for program implementers, the development of data-driven selection systems, and continuous evaluation are crucial to ensure that the KIP Kuliah program becomes more transparent, accountable, and effectively targeted. Keywords: Recruitment, Smart Indonesia Card (KIP Kuliah), Higher Education, Education Policy, Equity in Access.